2021
DOI: 10.1002/adom.202102250
|View full text |Cite
|
Sign up to set email alerts
|

Wafer‐Scale Growth of Vertical‐Structured SnSe2 Nanosheets for Highly Sensitive, Fast‐Response UV–Vis–NIR Broadband Photodetectors

Abstract: Owing to the strong light–matter interactions, 2D semiconducting thin films have shown their great potential in the development of high‐performance ultraviolet–visible–near infrared (UV–Vis–NIR) broadband photodetectors (PDs). However, the planar 2D semiconducting thin films via conventional growth method are often in the form of isolated flakes and/or suffering from low absorption efficiency of light, which hinders the UV–Vis–NIR optoelectronics from widespread applications. Herein are reported high‐performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…The high ON/OFF ratio facilitates this process and, as a result, the letters "SJTU" is successfully demonstrated using green (𝜆 = 532 nm, Figure 4d) and red (𝜆 = 727 nm, Figure 4e) light illumination at varying incident powers. Compared with similar array-level image-sensing devices based on BP, [29] Bi 2 O 2 Se, [30,31] MoS 2 , [32,33] and SnSe 2 , [34] the imaging contrast of the VP photodetector array is improved by 2-4 orders of magnitude. The successful array-level image-sensing demonstrations imply violet phosphorus is a promising candidate to fabricate the photodetector array with CMOS processing compatibility and realize low background noise and high-contrast target object imaging, trajectory tracking, etc.…”
Section: High-contrast Image-sensing Via the Vp Photodetector Arraymentioning
confidence: 99%
“…The high ON/OFF ratio facilitates this process and, as a result, the letters "SJTU" is successfully demonstrated using green (𝜆 = 532 nm, Figure 4d) and red (𝜆 = 727 nm, Figure 4e) light illumination at varying incident powers. Compared with similar array-level image-sensing devices based on BP, [29] Bi 2 O 2 Se, [30,31] MoS 2 , [32,33] and SnSe 2 , [34] the imaging contrast of the VP photodetector array is improved by 2-4 orders of magnitude. The successful array-level image-sensing demonstrations imply violet phosphorus is a promising candidate to fabricate the photodetector array with CMOS processing compatibility and realize low background noise and high-contrast target object imaging, trajectory tracking, etc.…”
Section: High-contrast Image-sensing Via the Vp Photodetector Arraymentioning
confidence: 99%
“…Currently, a variety of growth methods for low-dimensional nanomaterials have been reported, such as self-assembly [14], chemical vapor deposition [15], physical vapor deposition [16], and solution-liquid-solid methods [17]. Among these nanomaterials grown by various methods, IV-VI semiconductor nanomaterials with narrow band gaps, such as SnS [18,19], SnS 2 [20], SnSe 2 [21], and PbS [22], have been demonstrated promising in the field of optoelectronics and photonics applications.…”
Section: Introductionmentioning
confidence: 99%
“…6,[16][17][18] Recently, broadband photodetectors with a wide spectral photoresponse, as essential components of the modern integrated and miniaturized electronics industry, have received widespread attention for many technological applications, such as in imaging, optical communications, remote sensing, photoelectric memory, environment monitoring and military surveillance. [19][20][21][22] Moreover, the flexible characteristics of these device will expand their potential uses in human-machine interfaces and wearable applications. 23 It has been reported that crystalline disorder and oxygen vacancies in a-Ga 2 O 3 lead to a relatively narrow bandgap and a broad light absorption range.…”
Section: Introductionmentioning
confidence: 99%